Methodological Aspects of Assessment of Ecological and Economic Safety of Forestry (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The paper summarizes the scientific app roaches to the assessment of the environmental and economic safety of the enterprise. Further developed the methodological aspects of the assessment of environmental and economic safety of forestry, namely, to clarify the principles (development of purpose, scientific, systematic, consistency, stochasticity), criteria (for safety assessment in the short and long term) and approaches (resource, indicator, effective, system). In contrast to the existing maximum they take into account the specificity of forestry, the need to evaluate the short and long term, defining the role of environmental and resource components. Characterized the basic methods that can be used for this evaluation. The conditions of formation of information and analytical support for assessment of environmental and economic safety.
Keywords: ecological and economic safety, assessment of environmental and economic safety, forestry